Зэмос учыр: нылпиослы кылбуръёс, веросъёс / Эно Рауд - Рауд Эно (Эстон нылпи литература удмурт кылын, 2008)
Экземпляры: Ф. 4 (20201106) / Инвентарный номер: 42415 / Цена: 50.00 / Авт.знак: Р 25 / ГРНТИ: 17.82 / ББК: 84(4Эст)